Enhancing wave–particle duality - Arwa Bukhari; Daniel R E Hodgson; Sara Kanzi; Robert Purdy; Almut Beige (New Journal of Physics)
To enhance the consistency between the quantum descriptions of waves and particles, we quantise mechanical point particles in this paper in the same physically-motivated way as we previously quantised light in quantum electrodynamics (Bennett et al 2016 Eur. J. Phys. 37 014001). To identify the relevant Hilbert space, we notice that mechanical particles can occupy any position x while moving at any velocity v . Afterwards, we promote the classical states ( x ,  v ) to pairwise orthogonal quantum states $|x,v\rangle$ and demand that these evolve according to Newton’s equations of motion. The resulting quantum theory is mass-independent, when Newton’s equations of motion are mass-independent, as one would expect. The basic formulation of quantum mechanics emerges from quantum mechanics in configuration space as a semi-classical approximation when a fixed mass is imposed and several other adjustments are made.